Transexualidade: dos transtornos às experiências singulares - Araújo, Letícia Rezende de (2010)
This research questions the category of transsexuality in its psychopathologic dimension and the normative character concerning the sexual identities, which intend to inextricably connect sex, gender, sexual practice and desire. The implications of the sexual-anatomic and gender determinism in the process of the development of the subjectivities of the transsexuals are discussed; the pertinence of the Gender Identity Disorder (GID) psychiatric diagnosis for transsexuality is questioned; the psychoanalytic conceptions that support the psychosis diagnosis for transsexuality are analyzed; the possibility of sex change surgery subverting the sex-gender binary order is investigated; and finally, the implications of sex change surgery are considered in the subjectivities of the transsexuals. The data was collected and analyzed according to the qualitative research method and the semi-structured interview was used as the main instrument for the field research. The participants were male-to-female (MTF)transsexuals who had already undergone the surgery or were still waiting for the opportunity to do so. The data collection took place in the Gynecological Clinic in the Hospital das Clínicas da Universidade Federal de Pernambuco (UFPE) and the results were discussed in light of the theoretic contributions of Michel Foucault and Judith Butler, in the philosophical area, as well as those of Robert Stoller, Catherine Millot, Márcia Arán, Jurandir Costa and other contemporary authors, in the psychoanalytic area. The research results demonstrate that in deconstructing the normative conceptions inherent in the sex-gender binary system, the transsexuals transcend the limits of the psychopathologic certainties and, at the same time, confirm their subjectivities